AN EMPIRICAL ANALYSIS OF DIGITAL FINANCIAL SERVICE AND INCLUSIVE GROWTH AMONG RURAL WOMEN IN TAMIL NADU - K. V. Kiruthika; M. Jayanthi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study investigates the effect of digital payments on financial inclusion among rural women in Tamil Nadu, a state that has made significant progress in the adoption of digital finance. But still faces regional disparities. Secondary data were taken from Financial Inclusion Index (FII) published by RBI, MSME digital adoption statistics, NABARD Self-Help Group (SHG) reports, and Human Development Indicators, were used to analyses the performance at the district level. The methodology includes a combination of descriptive statistics, correlation, regression, and ANOVA to understand the relationships between digital adoption and financial inclusion. The findings indicate a strong positive correlation among the adoption of digital payments and financial inclusion. Regression analysis confirms that digital payment adoption, MSME participation, SHG involvement, and Human Development Index (HDI) are significant reflector of financial inclusion, accounting for nearly 84% of the variance. ANOVA results further reveal substantial differences in financial inclusion levels across districts with low, medium, and high digital adoption rates. The results shows that digital finance serves as a crucial catalyst for women’s financial inclusion, its effectiveness relies on supportive factors like literacy, participation in SHGs, and the presence of a robust MSME ecosystem. This study recommends the implementation of targeted digital literacy programs, the digitalization of SHGs, support for MSMEs, and the development of infrastructure in underperforming districts to enhance women’s financial empowerment and promote inclusive rural growth.